2021
DOI: 10.26650/jecs2021-863909
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Refugees' Entrepreneurship Motives and Challenges in Integration: Evidence From the Food Industry

Abstract: Understanding the role of refugees' entrepreneurship motives and challenges in integration: Evidence from the food industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 58 publications
(114 reference statements)
3
18
0
1
Order By: Relevance
“…While previous entrepreneurship success literature points out such personal traits as flexibility, satisfaction, growth and personal fulfillment (Walker and Brown, 2004), the current work demonstrates how motivation, personal background, integration and demographic characteristics of refugee entrepreneurs impact their business success. The present work also extends our understanding of how motivation shapes refugee entrepreneurs' success (Alrawadieh et al, 2021;Cifci and Atsiz, 2021;Cetin et al, 2022;Shneikat and Alrawadieh, 2019). It showed that integration is not only an outcome but an antecedent that triggers the success of refugee entrepreneurship.…”
Section: Theoretical Implicationssupporting
confidence: 72%
See 3 more Smart Citations
“…While previous entrepreneurship success literature points out such personal traits as flexibility, satisfaction, growth and personal fulfillment (Walker and Brown, 2004), the current work demonstrates how motivation, personal background, integration and demographic characteristics of refugee entrepreneurs impact their business success. The present work also extends our understanding of how motivation shapes refugee entrepreneurs' success (Alrawadieh et al, 2021;Cifci and Atsiz, 2021;Cetin et al, 2022;Shneikat and Alrawadieh, 2019). It showed that integration is not only an outcome but an antecedent that triggers the success of refugee entrepreneurship.…”
Section: Theoretical Implicationssupporting
confidence: 72%
“…IJCHM 36,4 Moreover, the work also contributes to the recent entrepreneurship strand by sampling a population with homogeneous characteristics (i.e. refugee entrepreneurs), which is overlooked in general entrepreneurship literature (Cuadros et al, 2023) and particularly in the T&H entrepreneurship field (Alrawadieh et al, 2019;Cifci and Atsiz, 2021;Fu et al, 2019). Additionally, it responds to a pending call from Cifci and Atsiz (2021) and Cetin et al (2022) for further investigations into refugee entrepreneurs' success in the T&H industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allowing refugees to participate and contribute socio-economically, rather than be dependent on government or UNHCR support, is an avenue to advance a more positive image of refugees thus boosting their integration and social-inclusion among host communities. Overall, integration also acts as an avenue to reduce the financial burden of hosting refugees to a host country (Atsız, 2021).…”
Section: Integration Social Economic Inclusion and Refugee Entreprene...mentioning
confidence: 99%